The potential of dynamic plants for attention and stress recovery in indoor environment. - Xu, Qianhao; Ding, Yifan; Li, Jian (Ergonomics, 2025)
This study simulates the natural movement of plants in indoor environments to investigate whether these plants can effectively facilitate psychological, physiological, and emotional recovery from fatigue caused by short vigilance tasks. A total of 63 participants completed baseline assessments of emotional and physiological stress as well as attention and memory (including the POMS-SF, blood pressure, pulse, and Digit Span Backward). They then performed a vigilance task to induce fatigue, followed by a second measurement of stress and cognition. After random assignment to dynamic plant, static plant, or no-plant conditions for a rest intervention, participants underwent a final assessment. The results showed that all three conditions experienced significant fatigue induced by the vigilance task, with increases in stress and reductions in cognition. Following the intervention, those in the dynamic plant condition exhibited notably greater recovery across multiple indices—particularly in emotional stress and pulse—than those in the other conditions. PRACTITIONER SUMMARY: In order to explore the effects of plant movement with the wind on people's attention and stress in the indoor environment, the results showed that the presence of indoor dynamic plants had a positive effect on cognitive, emotional, and stress recovery after the alertness task that induced fatigue.